Elevated Mirc1/Mir17-92 cluster expression negatively regulates autophagy and CFTR (cystic fibrosis transmembrane conductance regulator) function in CF macrophages. Issue 11 (1st November 2016) - Tazi, Mia F.; Dakhlallah, Duaa A.; Caution, Kyle; Gerber, Madelyn M.; Chang, Sheng-Wei; Khalil, Hany; Kopp, Benjamin T.; Ahmed, Amr E.; Krause, Kathrin; Davis, Ian; Marsh, Clay; Lovett-Racke, Amy E.; et al.
ABSTRACT: Cystic fibrosis (CF) is a fatal, genetic disorder that critically affects the lungs and is directly caused by mutations in the CF transmembrane conductance regulator (CFTR) gene, resulting in defective CFTR function. Macroautophagy/autophagy is a highly regulated biological process that provides energy during periods of stress and starvation. Autophagy clears pathogens and dysfunctional protein aggregates within macrophages. However, this process is impaired in CF patients and CF mice, as their macrophages exhibit limited autophagy activity. The study of microRNAs ( Mirs ), and other noncoding RNAs, continues to offer new therapeutic targets. The objective of this study was to elucidate the role of Mirs in dysregulated autophagy-related genes in CF macrophages, and then target them to restore this host-defense function and improve CFTR channel function. We identified the Mirc1/Mir17-92 cluster as a potential negative regulator of autophagy as CF macrophages exhibit decreased autophagy protein expression and increased cluster expression when compared to wild-type (WT) counterparts. The absence or reduced expression of the cluster increases autophagy protein expression, suggesting the canonical inverse relationship between Mirc1/Mir17-92 and autophagy gene expression. An in silico study for targets of Mirs that comprise the cluster suggested that the majority of the Mirs target autophagy mRNAs. Those targets were validated by luciferase assays. Notably, the ability of macrophages expressing mutant F508del CFTR to transport halide through their membranes is compromised and can be restored by downregulation of these inherently elevated Mirs, via restoration of autophagy. In vivo, downregulation of Mir17 and Mir20a partially restored autophagy expression and hence improved the clearance of Burkholderia cenocepacia . Thus, these data advance our understanding of mechanisms underlying the pathobiology of CF and provide a new therapeutic platform for restoring CFTR function and autophagy in patients with CF.